Analisis Rasio Keuangan dan Analisis Trend untuk Menilai Kinerja Keuangan pada PT. Sumera Jakarta Periode 2017-2021 - Br Karo, Adelina Wahyuni; Lasmana, Andy; Melani, Maria Magdalena (Karimah Tauhid, 2022)
The purpose of this study is to determine the financial performance and financial performance trends of PT Sumera Jakarta, which has used a ratio analysis of liquidity, solvency, activity and profitability over the past five years and trend analysis. Financial metrics analysis and trend analysis are performed to see the company's performance and trends. The data used is primary data and secondary data. This type of research is descriptively quantitative and aims to find facts from numbers. The subject of the study is the annual financial statements in the form of balance sheets and profit and loss accounst of PT. Sumera Jakarta for the period 2017-2021. The data analysis method used is a quantitative data analysis method. The results of the study, namely financial performance in terms of financial ratio analysis, namely liquidity consisting of the current ratio of 2019-2021, are categorized as in good condition and the quick ratio in 2020-21 is relatively good. Other ratios, namely solvency, activity and profitability, were concluded to be in a bad state. However, the trend of overall financial performance of the period under study is on average in an increasing or upward condition except for debt to total assets and net profit margin. Keywords: Financial performance, ratio analysis, trend analysis.